Kształtowanie relacji z klientami w turbulentnym otoczeniu - Piwoni-Krzeszowska, Estera (The creation of customer relations in a turbulent environment, 2007)
It seems that entrepreneurships aspiring to achieve success in a turbulent environment ought to take advantage of opportunities. Making profits of market possibilities needs a flexible attitude towards the customer relations creation. Entrepreneurships ought to concentrate on variable kinds of customers with regard to internal and external conditions determining the opportunities usage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 100-108